Retailing in the 21st Century Current and Future Trends - Krafft, Manfred; Mantrala, Murali K.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Retailing in the new millennium stands as an exciting, complex and critical sector of business in most developed as well as emerging economies. Today, the retailing industry is being buffeted by a number of forces simultaneously, e.g., increasing competition within and across retailing formats, the growth of online retailing, the advent of ‘radio frequency identification’ (RFID) technology, the explosion in customer-level data availability, the global expansion of major retail chains like Wal-Mart and METRO Group and so on. Making sense of it all is not easy but of vital importance to retailing practitioners, analysts and policymakers. With crisp and insightful contributions from some of the world’s leading experts, Retailing in the 21st Century is a compendium of state-of-the-art, cutting-edge knowledge for successful retailing today.
Overview -- Retail Success and Key Drivers -- Retailing in the Global World: Case Study of Metro Cash #x0026; Carry -- Entrepreneurship in Retailing: Leopold Stiefel#x2019;s #x201C;Big Idea#x201D; and the Growth of Media Markt and Saturn -- GLOBAL, ENVIRONMENTAL, AND MARKET TRENDS -- Retail Trends in Europe -- Trends in U.S. Retailing -- Trends in Retailing in East Asia -- Insights into the Growth of New Retail Formats in India -- Future Store Technologies and Their Impact on Grocery Retailing -- The Third Wave of Marketing Intelligence -- Applications of Intelligent Technologies in Retail Marketing -- New Automated Checkout Systems -- Understanding Retail Customers -- Future Trends in Multi-channel Retailing -- Retail Competition -- TRENDS IN RETAIL MANAGEMENT -- New Challenges in Retail Human Resource Management -- Retail Assortment: More #x2260; Better -- Out-of-Stock: Reactions, Antecedents, Management Solutions, and a Future Perspective -- Recent Trends and Emerging Practices in Retailer Pricing -- Retail Pricing #x2013; Higher Profits Through Improved Pricing Processes -- Current Status and Future Evolution of Retail Formats -- Electronic Retailing -- Supply Chain Management in a Promotional Environment -- Sales Promotion -- Understanding Customer Loyalty Programs -- Integrated Marketing Communications in Retailing.
Keywords: Marketing; Management; Industrial procurement; Marketing; Management; Procurement